Gazing at South African higher education transformation through the potential role of the Wesleyan quadrilateral: A theological approach - Hlatshwayo, Mlamuli N. (HTS teologiese studies, 2020)
The 2015–2016 South African higher education student movements evoked critical conversations regarding the extent to which institutions of higher learning have transformed into democratic and inclusive spaces. One of the key gaps in this field is the paucity of research that explores the potential role of theology in steering the direction of transformation in South African higher education system. Through a Wesleyan approach, the paper argues that the four quadrilaterals of the Wesleyn approach, scripture, tradition, reason and experience will be used as a theological tool to weight beliefs in the levels of dogma and doctrine, opinion and so as not to confuse critical reflection with negativity and judgmentalism in critically reflecting on the South African higher education struggles for transformation and decolonization. In our attempt to contribute meaningfully to the broader debates, started by scholars such as Nadar and Reddy (2015) and more recently, Phiri and Nadar (2018), who locate their work in theology to think through gender, curriculum and African feminism differently, counter-hegemonically. In this paper, we aim to contribute to this emerging body of work by arguing that theology has a critical role to play in helping us to imagine what a transformed, inclusive and socially just higher education could look like.